The singing planets [compact disc] : a musical adventure! - Wurst, Eric (Wonderscape, 2005)
Blast off on a musical adventure featuring twelve original songs that combine fun lyrics about the planets with memorable melodies for one big planet-hopping experience that's out of this world.